2010
DOI: 10.1577/t09-085.1
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Performance and Fishway Model Passage Success of Rio Grande Silvery Minnow

Abstract: We used a swim chamber, flume, and large-scale fishway models to assess the swimming performance, behavior, and passage success of endangered Rio Grande silvery minnow Hybognathus amarus. Field-captured silvery minnow (53-88 mm total length) swam 114-118 cm/s (i.e., up to 20.9 body lengths/s) in a swim chamber in water temperatures of 15, 19, and 238C. The relationship between time to fatigue and water velocity showed that endurance declined sharply at velocities above 60 cm/s, a threshold that is consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 48 publications
3
41
2
Order By: Relevance
“…In comparison, Pecos bluntnose shiner exhibited higher swimming capacity (U crit, 52.5 cm·s −1 ) at 90 days posthatch. Bestgen et al (2010) reported upper critical swimming speeds of 51.5 cm·s −1 (53-75 mm TL) for Rio Grande silvery minnow, noting that swimming ability increased with fish size. Although Pecos bluntnose shiner demonstrated strong swimming ability and upriver movement, downriver dispersal of propagules has potentially tripled to distances up to 142 km from predam-prechannelization of the river (Dudley and Platania 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Pecos bluntnose shiner exhibited higher swimming capacity (U crit, 52.5 cm·s −1 ) at 90 days posthatch. Bestgen et al (2010) reported upper critical swimming speeds of 51.5 cm·s −1 (53-75 mm TL) for Rio Grande silvery minnow, noting that swimming ability increased with fish size. Although Pecos bluntnose shiner demonstrated strong swimming ability and upriver movement, downriver dispersal of propagules has potentially tripled to distances up to 142 km from predam-prechannelization of the river (Dudley and Platania 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These problems are commonly associated with private and public infrastructure such as dams, culverts, water diversions, and grade control structures (Castro-Santos et al, 2009;Dermisis and Papanicolaou, 2009;Norman et al, 2009;Castro-Santos and Haro, 2010;Martens and Connolly, 2010;Hall et al, 2011). Often this infrastructure disrupts or prohibits natural fish movement patterns, fragments fish habitat, degrades populations, and influences overall biotic structure of aquatic systems (Pratt et al, 2009;Bestgen et al, 2010;Bouska and Paukert, 2010;Castro-Santos and Haro, 2010;Hall et al, 2011). The restricted ability to access needed habitats has even led to the demise of some fish populations (Zheng et al, 2009;Castro-Santos and Haro, 2010;Hall et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies allow precise control of experimental conditions and examination of the effects of variables such as fish length and morphology, temperature and water velocity on swimming performance. The majority of laboratory studies have been conducted in small enclosed swim chambers and have examined the time to fatigue at a set velocity (Billman & Pyron, ; Bestgen et al , ; Ficke et al , ) or the maximum aerobic swimming speed using an incremental velocity test ( U crit test) in which the velocity is incrementally increased and time to failure at the maximum velocity is measured (Nelson et al , ; Holthe et al , ; Leavy & Bonner, ). Recent studies, however, have suggested that space constraints in swim chambers may restrict volitional behaviour and the ability of fishes to utilize different muscle groups, thereby resulting in an underestimation of swimming abilities (Tudorache et al ., , ; Castro‐Santos et al , ; Sanz‐Ronda et al , ).…”
Section: Introductionmentioning
confidence: 98%